Evaluating the concordance between Vesical Imaging Reporting and Data System scores and bladder tumor histopathology - Hasan Gungor; Ahmet Camtosun; Ibrahim Topcu; Leyla Karaca (Asian Journal of Urology)
Objective: This study aimed to assess the local staging of bladder tumors in patients utilizing preoperative multiparametric MRI (mpMRI) and to demonstrate the clinical efficacy of this method through a comparative analysis with corresponding histopathological findings. Methods: Between November 2020 and April 2022, 63 patients with a planned cystoscopy and a preliminary or previous diagnosis of bladder tumor were included. All participants underwent mpMRI, and Vesical Imaging Reporting and Data System (VI-RADS) criteria were applied to assess the recorded images. Subsequently, obtained biopsies were histopathologically examined and compared with radiological findings. Results: Of the 63 participants, 60 were male, and three were female. Categorizing tumors with a VI-RADS score of >3 as muscle invasive, 84% were radiologically classified as having an invasive bladder tumor. However, histopathological results indicated invasive bladder tumors in 52% of cases. Sensitivity of the VI-RADS score was 100%; specificity was 23%; the negative predictive value was 100%; and the positive predictive value was 62%. Conclusion: The scoring system obtained through mpMRI, VI-RADS, proves to be a successful method, particularly in determining the absence of muscle invasion in bladder cancer. Its efficacy in detecting muscle invasion in bladder tumors could be further enhanced with additional studies, suggesting potential for increased diagnostic efficiency through ongoing research. The VI-RADS could enhance the selection of patients eligible for accurate diagnosis and treatment.